Application of fuzzy logic hierarchical network methods for risk assessment of industrial enterprise - A. Y. Belozersky; O. V. Bulygina (Путеводитель предпринимателя)
The article considers the importance of risk management in the corporate system of industrial enterprise, substantiates the choice of data mining techniques and suggests the conceptual model of risk assessing internal and external enterprise environment using fuzzy-logic hierarchical network tools.